1999
DOI: 10.1016/s0008-6363(99)00074-7
|View full text |Cite
|
Sign up to set email alerts
|

New look at myocardial infarction: toward a better aspirin

Abstract: The evidence for the formation of NO and of its oxidation products, as well as of prostacyclin and thromboxane by the infarcted heart muscle is reviewed. The importance of inflammatory cells, primarily macrophages of cardiac origin is documented. Because of its side effects on gastric mucosa and kidney by aspirin, several modifications of aspirin are currently being developed. These are based on eliminating their inflammatory effect by selective inhibition of COX-2, or by attaching an NO-delivering side chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Therefore, inhibition of TXA 2 counteracts these effects. Reduction of PGI 2 synthesis by celecoxib could interfere with the coronary vasodilator effect of PGI 2 [16]. Since macrophages are located at the border area of the infarcted region, the activity of prostanoids on the infarcted region is secondary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of TXA 2 counteracts these effects. Reduction of PGI 2 synthesis by celecoxib could interfere with the coronary vasodilator effect of PGI 2 [16]. Since macrophages are located at the border area of the infarcted region, the activity of prostanoids on the infarcted region is secondary.…”
Section: Discussionmentioning
confidence: 99%
“…10 B-NOD accomplishes this through NO release, which increases prostaglandin formation. 15 B-NOD has potential clinical relevance because the release of NO counters the diminution of prostacyclin by aspirin and thereby inhibits platelet aggregation (Figures 1 and 2, Table). Deterioration of renal function by selective COX-2 inhibitors has been repeatedly demonstrated.…”
Section: Nsaids and B-nodmentioning
confidence: 99%
“…The beneficial effects of aspirin are ascribed to its inhibition of platelet aggregation and inhibition of thromboxane generation by COX-1. 4 A mounting body of data, however, suggests that inhibition of COX-2 enhances cell death, particularly apoptotic cell death. 5,6 It has recently been suggested that apoptosis may play a role in ischemia/reperfusion injury.…”
mentioning
confidence: 99%